Analisis AISAS Penggunaan Brand Ambassador dalam Komunikasi Pemasaran Digital Realfood - Utami, Sindy Masta; Mardiana, Lisa; Kumalasari, Astini (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
AbstractThe use of brand ambassadors in Indonesia has shown a significant increase in recent years. Many companies in Indonesia have switched to using brand ambassadors and public figures to promote products in order to increase consumer buying interest, this is due to the increasing level of competition so that it is increasingly competitive. Based on this, Realfood conducts a marketing communication strategy to maintain its existence by collaborating with celebrities from South Korea as brand ambassadors in mini content advertisements. The method applied in this research is descriptive qualitative research method and uses two data sources, namely primary data sources secondary data. Primary data is collected by researchers directly through the interview and observation process, while secondary data is obtained through journals and observations. The results of this study indicate that, the use of brand ambassadors can influence consumer attention (attention), arouse buying interest (interest), and make consumers to find out information (search), encourage consumer action (action) to interact and share information (share) related to Realfood products.Keywords: Brand Ambassador, Realfood Advertising, Consumer Purchase Interest, AISAS